Avaliação experimental do reinício de escoamento de solução aquosa de Laponita® RD - Duarte Junior, Roque Martins (2020)
During crude oil production, oil reservoirs can reach up to 7,000 meters of depth. The oil pressure and temperature in these conditions can reach up values of 100 MPa and 150 °C, respectively, while the seabed is approximately at 4 °C. Thus, during the production and transportation of crude oil from these reservoirs to the shore, which occurs through pipelines, the oil is subject to high temperature gradients. This temperature difference causes the oil to cool down, causing the crystallization of the paraffin crystals and, consequently, the oil gels in the pipeline. Under these conditions, the oil has a non-Newtonian behavior such as viscoplasticity, elasticity, temporal and shear history dependence. In order to restart the flow of the gelled material, it is necessary to impose higher pressures than the ones used during production. If the pressures are too high, the pipelines may be damaged causing economic and environmental problems. Understanding the influence of each rheological parameter during the startup is a difficult task due to the complexity of the oil. Therefore, in order to experimentally investigate the influence of the time dependence (thixotropy) on the flow startup phenomenon, it was used a model thixotropic material, which consists in an aqueous solution of Laponite® RD with a concentration of 2 wt%. To evaluate the material behavior the following tests were performed: flow curve, flow rate and pressure steps, flow startup with different resting times and visualization by flow rate imposition. The tests were carried out in a laboratory-scale flow loop with a long helical pipeline placed in a thermally insulated chamber. Through the flow curve it was possible to characterize the rheological behavior of a shear thinning yield-stress fluid in the steady-state regime. The flow rate steps test confirmed the dependence on the shear history of the material. Besides that, the flow startup demonstrated that the increase in the resting time delays the restart and increases the overshoot pressure reached. In the flow startup test with visualization and in the pressure steps, it was verified that the minimum stress that the material flows is similar to the yield-stress obtained through the flow curve. Finally, it was observed that an increase in the resting time and aging of Laponite® induced the appearance of partial breaking in the gelled structure during the flow startup tests.